Cooperativas de crédito e bancos: uma análise comparativa envolvendo a percepção dos cooperados/correntistas sobre o ser cooperado ou não - Marion, Patrícia (My University, 2021)
This paper presents a comparison between credit unions and banks, with a view to highlighting the perception of being cooperated or not, as well as exploring the interviewees' understanding of Capital Quota, Educational and Social Technical Assistance Fund (ESTAF), and their rights and duties in the two financial institutions. The credit union have been growing over time, as it is different from traditional banking institutions, as it is not aimed at profit, but rather at delivering cooperative value to its users. In that case, the return of the value of the cooperative is linked to the mission of valuing the relationship with the cooperative member. To achieve the proposed objective, the descriptive research methodology was used, developing a case study with a quantitative and qualitative approach. The collection of information was obtained by applying questionnaires to the cooperative members of Cooperativa Cresol (credit union) and Banco do Brasil (bank), in the city of Nova Bassano - RS. The results obtained indicated the need for the cooperative to invest more in the cooperative education of its members. The research showed, based on the interviewees' considerations, that being cooperated is relevant and that there is a difference between a cooperative and a bank. The research had limitations related to identifying the effective use of ESTAF by Cooperativa Cresol, since the questions in the questionnaire did not directly relate this issue. It is suggested, for future studies, more research that can relate other credit unions and banking institutions, or even build comparisons only between credit unions. [resumo fornecido pelo autor]
Este trabalho apresenta um comparativo entre as cooperativas de crédito e os bancos, com vistas a evidenciar a percepção do ser cooperado ou não, além de explorar o entendimento dos entrevistados a respeito de Cota Capital, Fundo de Assistência Técnica Educacional e Social (FATES), e seus direitos e deveres nas duas instituições financeiras. O cooperativismo de crédito vem crescendo com o tempo, pois é diferente das instituições bancárias tradicionais, uma vez que não visa o lucro, mas sim a entrega de valor cooperativista aos seus usuários. Nesse sentido, a entrega do valor da cooperativa está atrelada à missão de valorizar o relacionamento com o cooperado. Para alcançar o objetivo proposto foi utilizada a metodologia de pesquisa descritiva, efetuando um estudo de caso com abordagem quantitativa e qualitativa. A coleta das informações foi obtida mediante aplicação de questionários aos cooperados da Cooperativa Cresol e do Banco do Brasil, do município de Nova Bassano - RS. Os resultados obtidos indicaram a necessidade de a cooperativa investir mais na educação cooperativista de seus cooperados. A pesquisa evidenciou, a partir de considerações dos entrevistados, que ser cooperado é relevante e, ainda, que há diferença entre cooperativa e banco. A pesquisa apresentou limitações relacionadas a identificar o efetivo uso do FATES pela Cooperativa Cresol, uma vez que as questões do questionário não relacionaram diretamente este assunto. Sugerem-se, para estudos futuros, mais pesquisas que possam relacionar outras cooperativas de crédito e instituições bancárias ou, ainda, construir comparativos somente entre cooperativas de crédito. [resumo fornecido pelo autor]
Keywords: Contabilidade; Cooperativas; Bancos